Sosialisasi dan Edukasi Pemilahan Sampah Organik dan Anorganik dalam Menanamkan Kesadaran Lingkungan pada Siswa Sekolah Dasar - Azizah, Annafi’ Nurul ‘Ilmi; Sugiyat, Sugiyat; Nuruddien, Muhammad; Musfirah, Atikah; Muthaharah, Rillia Marfuatim; Pangestika, Afifah Sekar; Awali, Masfufah Zayin; Walhidayah, Nanda Ayu (CV. Devi Tara Innovations, 2026)
Waste management remained an environmental issue that required early awareness building, particularly at the elementary school level. This community service activity aimed to foster environmental awareness among students through socialization and education on organic and inorganic waste separation at SD Negeri Keloran 2. The activity was conducted on 19 January 2026 and involved 40 fifth-grade elementary school students as participants. The program was implemented using an educational and participatory approach, which included interactive material delivery, educational games, and practical reuse activities. The activity began with the presentation of material explaining the definition, types, and proper methods of waste separation in daily life. This was followed by educational games designed to reinforce students’ understanding of waste classification. The activity concluded with a hands-on practice of creating handicrafts from used cardboard as an application of reuse principles. The results indicated that students were able to distinguish between organic and inorganic waste and demonstrated increased awareness and concern for environmental cleanliness within the school environment. Overall, the activity contributed positively to shaping environmentally responsible behavior from an early age and showed potential for supporting sustainable waste management practices in elementary schools.